Can Lipoprotein(a) Predict the Risk of Diabetic Nephropathy in Type 2 Diabetes Mellitus?: A Systematic Review and Meta-Analysis - Wu, Feixiang; Cui, Chenmin; Wu, Junping; Wang, Yunqing (Hormone and Metabolic Research, 2025)
We aimed to examine if serum lipoprotein(a) [Lp(a)] values could be used to predict the risk of diabetic nephropathy (DN) in type 2 diabetes mellitus (T2DM). English-language observational studies available as full-texts on PubMed, Embase, Scopus, and Web of Science databases up to 28th November 2024 were included in the review. Studies were to assess the association between Lp(a) and DN and report adjusted effect size. Random-effects meta-analysis was conducted. Five cross-sectional, two case-control, and eight studies prospective cohort were included. Six studies used Lp(a) as a continuous variable while eight used it as a categorical variable. Two studies used Lp(a) as both. Meta-analysis showed that an incremental increase in Lp(a) was associated with a small increase in the risk of DN (OR: 1.03 95% CI: 1.01, 1.04 I2=86%). Meta-analysis also showed that high levels of Lp(a) were associated with a significant increase in the risk of DN (OR: 1.64 95% CI: 1.24, 2.17 I2=67%). Subgroup analysis based on study design, location, sample size, T2DM duration, baseline HbA1c, and definition of DN yielded mixed results. Lp(a) could be a potential marker for DN in T2DM. Further investigations may provide better evidence.
Keywords: lipids; diabetic kidney disease; renal dysfunction; microvascular complications